Structural Empirical Evaluation of Job Search Monitoring - Gerard J. van den Berg; Bas van der Klaauw (Institute for the Study of Labor (IZA), 2013)
We structurally estimate a novel job search model with endogenous job search effort, job quality dispersion, and effort monitoring, taking into account that monitoring effects may be mitigated by on-the-job search and search channel substitution. The data are from a randomized experiment conducted in the Netherlands. They include registers of post-unemployment outcomes like wages and job mobility, and survey data on measures of search behavior. As such we are the first to study monitoring effects on post-unemployment outcomes. We find that the option to climb the job ladder reduces substitution between search channels during unemployment and compensates for adverse long-run effects of monitoring on wages. We use the structural estimates to compare monitoring to counterfactual policies against moral hazard, like re-employment bonuses and changes in the unemployment benefits path. Replacing monitoring by an overall benefits reduction in a way that is neutral to the worker results in slightly smaller effects with lower administrative costs.
Keywords: J64; J65; J68; J62; D83; D82; C31; C32; 330; unemployment duration; search effort; active labor market policy; wage; job duration; job mobility; treatment; search channels; multi-tasking; randomized social experiment